Motor neuron disease after electric injury. Issue 2 (1st August 2001) - Jafari, H; Couratier, P; Camu, W
Abstract : The occurrence of motor neuron disease after electrical injury in six patients is reported and compared with patients from the literature. The patients were five men with spinal onset and one woman with bulbar motor neuron disease after electric shock. Two patients were struck by lightning and four by industrial electric shock. For all six of them, the disease started at the site of the electrical trauma. The mean delay for onset of motor neuron disease was 44 months. In four of the spinal patients the disease progressed slowly with mild handicap after several years. For the fifth patient, improvement was noted progressively. The patient with bulbar disease died 26 months after onset. A link between electric shock and motor neuron disease is likely, given the homogenous profile of the patients both in the five spinal cases presented here and in the literature. Bulbar onset has not been reported to date. However, in this patient the long delay between the electrical injury and motor neuron disease, together with the rapid evolution may suggest a chance association.